Uji Aktivitas Antioksidan dan Profil Fitokimia Biji Kopi Robusta (Coffea canephora), Biji Vanili (Vanila planifolia), dan Kombinasi Keduanya dengan Bermacam Pelarut: Tests of Antioxidant Activity and Phytochemical Profile of Robusta Coffe Seeds (Coffe canephora), Vanilla Seeds (Vanila planifolia), and the Combination of the Both With Various Solvents - Muhammad Andre Niljon; Himmi Marsiati (Jurnal Surya Medika (JSM), 2023)
Robusta coffee (Coffea canephora) and vanilla fruit (Vanila planifolia) are plants that contain antioxidants. The aim of the study was to determine the antioxidant activity of these plants and their combination. Activity was measured using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method on ethanol, ethyl acetate, and water extracts. The results of the research on vanilla fruit had an IC50 value of 153.09 ppm in ethanol extract, IC50 176.69 ppm in ethyl acetate extract, and IC50 245.28 ppm in aqueous extract. Robusta coffee beans have an IC50 value of 18.96 ppm in the ethanol extract, an IC50 of 27.03 ppm in the ethyl acetate extract, and an IC50 of 20.13 ppm in the aqueous extract. The combination of vanilla and coffee had an IC50 value of 39.40 ppm for the ethanol extract, an IC50 of 41.25 ppm for the ethyl acetate extract, and an IC50 of 38.60 ppm for the aqueous extract. Vitamin C as a standard for comparison has an IC50 value of 2.99 ppm. The ANOVA test results showed a value of p <0.05 which indicated that there were significant differences between samples with various solvents. Phytochemical tests showed that vanilla contain flavonoids and phenolics.